Root-applied brassinosteroid and salicylic acid enhance thermotolerance and fruit quality in heat-stressed ‘Kyoho’ grapevines - Sun, Yanli; Sun, Sijie; Zahid, Muhammad Salman; Qiu, Qian; Wang, Lei; Wang, Shiping (Frontiers in Plant Science, 2025)
IntroductionThe increasingly severe global greenhouse effect has become an irreversible trend, significantly impacting viticulture regions through heat stress during various grape growth stages, especially under protected cultivation conditions where high temperatures frequently occur. Therefore, studying the impact of heat stress on grapevine growth and fruit quality across the entire growth and development period, along with effective mitigation measures, is crucial.MethodsIn this study, three-year-old 'Kyoho' grapevines were used as experimental materials, with four treatment groups: a control group, a hightemperature group (heat stress, HT), a high-temperature + brassinolide group (BR), and a high-temperature + salicylic acid group (SA). During the flowering, young berry swelling, and veraison stages, BR and SA were applied via nutrient solutions every seven days.ResultsThe results demonstrated that BR restored the maximum photosynthetic rate (Amax) to 96.14% of CK by the 18th day of flowering, significantly outperforming SA's recovery rate of 86.64%. Both treatments maintained light saturation points (1200 μmol•m⁻²•s⁻¹) and CO2 saturation thresholds equivalent to CK. The decline in PSII photochemical efficiency (Fv/Fm) was reduced from 18% in HT to 5–8% in BR/SA-treated groups, with BR showing minimal deviation (2.3%) from CK during veraison, effectively mitigating PSII photoinhibition caused by heat stress. Furthermore, both treatments reduced leaf malondialdehyde (MDA) content, minimizing membrane lipid peroxidation, while increasing soluble protein (SP) content to protect leaves. Under heat stress, BR notably improved the fruit set rate by 22.67% compared to HT (SA: 13%), promoted berry expansion, and enhanced the accumulation of sugars and anthocyanins in the fruit skin, with SA showing similar, though slightly less pronounced, effects.DiscussionThese findings provide valuable theoretical insights into the use of exogenous hormones in root nutrient solutions as a strategy to mitigate the adverse effects of heat stress in grape production.